Owning and operating costs of motorcycles in Malaysia - Norshahira, Adom (2017)
This project is a researched about Owning and Operating Cost of Motorcycles in Malaysia. In case study, a method of study has been done, which is to key-in the data collected from questionnaire that has been distributed into Microsoft Excel to get the kilometre used per year for every motorcycles. The data collection consists of various type of motorcycles, capacity engine of motorcycles, year of manufactures and kilometre used for motorcycles. So, from the data collected, the results and analysis were obtained which are the total cost of owning and operating cost of motorcycles. Besides that, the data were collected among the student in UMP and people that using motorcycles around Malaysia. Last but not least, as a conclusion, Owning and operating cost of motorcycles is depending on type of motorcycles used and capacity of engine used.